Predictors of Prolonged Grief Disorder in a German Representative Population Sample: Unexpectedness of Bereavement Contributes to Grief Severity and Prolonged Grief Disorder - Doering, Bettina K.; Barke, Antonia; Vogel, Anna; Comtesse, Hannah; Rosner, Rita (Frontiers in Psychiatry, 2022)
Most people adapt to bereavement over time. For a minority, the grief persists and may lead to a prolonged grief disorder (PGD). Identifying grievers at risk of PGD may enable specific prevention measures. The present study examined the extent to which the subjective unexpectedness of the death predicted grief outcomes above and beyond known sociodemographic and objective loss-related variables in a sample drawn from a population-representative investigation. In a sample representative of the German population (n=2531), 811 participants (Mage 55.1±17.8 years, 59.2% women) had experienced the loss of a signiﬁcant person six or more months ago. Participants provided demographic and loss-related information, perceptions of the unexpectedness of the death and completed the Prolonged Grief Disorder-13+9 (PG-13+9). The PG-13+9 was used to determine PGD caseness. A binary logistic regression investigated predictors of PGD caseness, and a linear regression predictors of grief severity. ANCOVAs compared PGD symptoms between the groups who had experienced an ‘expected’ vs. ‘unexpected’ loss, while controlling for the relationship to the deceased and time since loss. The loss of a child (OR=23.66; 95%CI, 6.03-68.28), or a partner (OR=5.32; 95%CI, 1.79-15.83), the time since loss (OR=0.99; 95%CI, 0.99-1.00) and the unexpectedness of the death (OR=3.58; 95%CI, 1.70-7.69) were significant predictors of PGD caseness (Nagelkerke’s R²=.25) and grief severity. Participants who had experienced the loss as unexpected (vs expected) reported higher scores on all PGD symptoms. Unexpectedness of the death was associated with all PGD symptoms and emerged as significant risk factor for PGD, even after controlling for demographic and other loss-related variables. While our findings replicate previous research on the importance of the relationship to the deceased as a risk factor for PGD, they also highlight the importance of assessing the subjective unexpectedness of a death and may help to identify risk groups who can profit from preventive interventions.